The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd004081.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine for preventing postoperative sore throat

Abstract: Our systematic review establishes the effectiveness of topical and systemic lidocaine for the prevention of postoperative sore throat resulting from intubation. The risk and severity of postoperative sore throat tended to be reduced. The effect size of lidocaine appeared to be affected by drug concentration and route of administration; management of cuff pressure during anaesthesia; the included population; and the type of outcome measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 31 publications
3
37
0
1
Order By: Relevance
“…20 Lidocaine has also been used to break post-extubation stridor and laryngospasm in adult patients 19,21 and to decrease postoperative sore throat after extubation. 22 Although most of these studies refer to adult patients, the present results in pediatric patients are consistent with these findings. Even though lidocaine is a relatively short-acting local anesthetic, we could show an effect of local application on the postoperative and overall complication rate.…”
Section: Discussionsupporting
confidence: 90%
“…20 Lidocaine has also been used to break post-extubation stridor and laryngospasm in adult patients 19,21 and to decrease postoperative sore throat after extubation. 22 Although most of these studies refer to adult patients, the present results in pediatric patients are consistent with these findings. Even though lidocaine is a relatively short-acting local anesthetic, we could show an effect of local application on the postoperative and overall complication rate.…”
Section: Discussionsupporting
confidence: 90%
“…As shown in table 2, the severity of post-intubation sore throat was significantly reduced in patients receiving tetracaine as inflation medium, compared with patients receiving other inflation media (P<0.05), at 6 (primary outcome), 24 and 48 (secondary outcomes) hours after extubation. As previously reported (20), lidocaine, per se, could reduce sore throat when compared with normal saline or air (P<0.05).…”
Section: Resultssupporting
confidence: 82%
“…It can also be due to the osmolarity of the jelly since mucosal irritation can depend on the osmolarity of the lubricant [18]. But some other studies have shown a better result with the use of lidocaine [19]. Our significant finding at 24 h may also be due to prolonged action of betamethasone gel while the effect of lidocaine wears off earlier, producing a wider gap in the incidence and severity score at 24 h.…”
Section: Discussionmentioning
confidence: 68%